Ex Vivo Cytokine Profiling of Cryptococcus neoformans Strains Suggests Strain-Specific Immune Modulation: A Cross-Sectional Study - Kennedy Kassaza; Fredrickson B. Wasswa; Kirsten Nielsen; Joel Bazira (Cureus, 2025)
Cryptococcal meningitis (CM) remains a major cause of mortality among people living with human immunodeficiency virus (HIV), especially in sub-Saharan Africa. The interplay between fungal genotype and host immune response is critical in determining disease outcome. We conducted ex vivo cytokine profiling using peripheral blood from HIV-positive and HIV-negative adults stimulated with heat-inactivated whole cell antigens from two Cryptococcus neoformans strains: the reference strain H99 and the genetically distinct UgCl377 clinical strain. These strains differ at multiple loci, including the CNAG_04922 gene. Luminex based quantification revealed that H99 induced significantly higher levels of CD40-ligand, IL-10, IL-12p70, IL-13, IL-15, and IL-33. These cytokines reflect pro-inflammatory, Th2, and regulatory responses, suggesting robust immune activation. In contrast, the UgCl377 strain elicited a dampened cytokine profile. While this study does not isolate the effect of CNAG_04922 alone, it demonstrates that whole-cell antigens from genetically distinct strains of C. neoformans elicit differential cytokine responses. These findings provide a foundation for future mechanistic studies using purified proteins or isogenic strains.
Keywords: Cnag_04922; Cryptococcal meningitis; Cryptococcosis; Cryptococcus neoformans; Cytokine response; Gene alleles; Host-pathogen interaction; Pro-inflammatory cytokines; single nucleotide polymorphism; Tnf-alpha